Wear estimation of trapezoidal and circular shaped hip implants along with varying taper trunnion radiuses using finite element method. (November 2020) - K N, Chethan; Ogulcan, Guldeniz; Bhat N, Shyamasunder; Zuber, Mohammad; Shenoy B, Satish
Highlights: Wear in the articulating surfaces is the main reason for the revision surgery of hip implants. ANSYS is used to estimate the linear wear rate at the taper trunnion interface against varying the taper trunnion top surface geometry. Circular and trapezoidal-shaped stem implants are used for the analysis. The results revealed that the taper trunnion dimension of 12/14 mm of circular-shaped implant has the least linear wear rate of 0.003 mm/year. Trapezoidal shaped implant with a taper trunnion interface of 8/14 mm has the highest linear wear rate of 0.397 mm/year. This study helps to estimate the linear wear rate in any articulating surfaces using ANSYS. Abstract: Background and objective: The hip joint is the vital joint that is responsible for the bodyweight transfer from the upper body to the lower body. Due to age these joints are worn out and need to be replaced by artificial hip implants. Wear is the predominant factor that is responsible for the loosening of hip implants. The wear occurs between the joints due to various reasons. The wear estimation at the design stage gives a clear idea about the life of the implants and also minor changes in the design may also significantly increase the life expectancy of the implant which can further reduce the rate of revision surgery. The linear wear rate is estimated in the taper trunnion surface. Methods: In this study, the circular and trapezoidal-shaped stem implant is designed, and wear studies are performed at the trunnion junction. The femoral head of size 28 mm, acetabular cup thickness of 4 mm, and a backing cup of thickness 2 mm are considered for the study. The neck taper radiuses at the top surface are altered. Ansys is used to perform the simulations. Results: At the time of assembly of the femoral head into the stem, the stresses were found to be increasing with an increase in the top surface radius of the neck taper junctions. However, when the walking conditions are considered for wear estimation of implants the circular implants with the 12/14 mm taper exhibited the lesser linear wear rate of 0.003 mm/year. The trapezoidal implants with the 10/14 mm taper exhibited a lesser linear wear rate of 0.032 mm/year. Conclusions: Wear is an important parameter that leads to the revision of implants due to loosening. It is found that with the decrease in the taper radius at the top surface against the standard 12/14 mm taper there is no significant decrease in the wear rate at the taper junction. Overall the circular implants exhibited less wear rate results over the trapezoidal-shaped stem implants. Due to the less linear wear rate, the circular implant has a higher life over the trapezoidal-shaped implant. Further, these implants can be manufactured to test using a hip simulator with the same conditions to validate the obtained results.